Influence of the presence and type of fragrance on the sensory perception of cosmetic formulations - Gonçalves,Gisele Mara Silva (2013)
The aim of the present study was to evaluate the sensory assessments of identical cosmetic formulations with and without fragrance to investigate not only the acceptance but also how different fragrances affected their attributes, such as skin feel, tackiness and spreadability. Three gel and three cream formulations with and without two types of fragrance, fennel and sweet flowers, were assessed for various attributes. The presence and type of fragrance used affected the testers' perception of some attributes, showing that the influence of this component should not be disregarded. Apparently, a consumer's reaction to a cosmetic product is not only based on its efficacy but also on how its attributes are perceived, such as appearance, skin feel and smell.